PENGGUNAAN DEIKSIS BAHASA JAWA DALAM INTERAKSI SOSIAL PADA GRUP FACEBOOK INFO SEPUTAR JUWIRING, KLATEN: KAJIAN PRAGMATIK - Syaifudin, Nanang (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
This study examines the use of Javanese deixis in social interactions within the Facebook group Info Seputar Juwiring, Klaten , using a pragmatic approach. Deixis is a crucial element in communication that depends on the context of conversation, including person, place, time, and social deixis. The study aims to identify the types of deixis used and analyze the pragmatic functions embedded in their usage. Using a descriptive qualitative approach, data were collected through purposive sampling from 56 comments posted by group members during December 2024. The analysis revealed that social deixis had the highest frequency (48.2%), followed by person deixis (23.2%), place deixis (16.1%), and time deixis (12.5%). The findings indicate that group members use Javanese language to assert social identity, maintain social relationships among members, and convey information relevant to the local community. This research provides new insights into the adaptation of regional languages in digital communication and enriches the study of pragmatics and deixis usage in social media.